Heart rhythm disorders: History, mechanisms, and management perspectives - Gomes, J. A. (Springer Nature, 2020)
This engaging book covers a multitude of topics related to heart rhythm disorders (HRDs) and uniquely familiarizes readers with the development of treatment modalities over the past several decades, including the evolution of anti-arrhythmic drugs, pacemakers, defibrillators, and catheter ablation.